Surface functionalization of Polymers of Intrinsic Microporosity (PIMs) membrane by polyphenol for efficient CO2 separation - Zhong Gao; Yanan Wang; Hong Wu; Yanxiong Ren; Zheyuan Guo; Xu Liang; Yingzhen Wu; Yutao Liu; Zhongyi Jiang (Green Chemical Engineering, 2021)
Membrane separation technology offers a green, efficient and energy-saving approach for biogas upgrading. Membranes with high selectivity and high permeability are the key to achieve high performance. Polymers of Intrinsic Microporosity (PIMs) materials have shown excellent gas permeability but low selectivity which limits their practical application. Herein, a polyphenol, tannic acid, was coated on the PIM-1 membrane surface by a facile dipping method to fabricate composite membranes. Tannic acid containing a large number of polar oxygen-containing groups (quinone, phenolic hydroxyl) self-polymerized on the membrane surface to form a CO2-philic, defect-free and thin layer. The CO2/CH4 selectivity of the resultant composite membranes was increased after tannic acid coating while the permeability remained comparable to or even higher than pristine PIM-1 membrane, exceeding the reported 2008 upper bound.